POTRET PERUBAHAN PROFITABILITAS 16 BANK UMUM DI BURSA EFEK INDONESIA PADA PERIODE 2011-2016 - Ayu Intan Anggraeni, 13.05.51.0176 (Students' Journal of Economic and Management, 2017)
This study aims to examine and analyze the influence of variables the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Operational Cost Ratio to Operational Income (BOPO), and Net interst Margin (NIM) of the Return On Asset (ROA) on Commercial Bank listed in the Indonesia Stock Exchange (IDX) on the period 2011-2016. The population in this study is a commercial bank listed in the Indonesia Stock Exchange (IDX) from 2011 until 2016. The samples are determined using purposive sampling. The criteria used are commercial bank listed on the Stock Exchange in 2011 - 2016 and the banks submit annual financial statements and completely. Method of data analysisused is panel data regression with selectionbetwenestimation method Fixed Effect Model (FEM) and the Random Effect Model (REM) through the Hausman Test. Hausman Test result of this study recommends using model REM. Based on the ouput, the largest constant value is found in Bank Rakyat Indonesia, Tbk and the smallest constant value is in Bank Negara Indonesia, Tbk.Based on the output Random Effect Model (REM) showed that CAR has no effect on ROA, NPL has a significant negative effect on ROA, LDR has no effect on ROA, BOPO has a significant negative effect on ROA, and NIM has a significant positive effect on ROA.The ability of the independent variables to explain ROA changes in Commercial Banks listed on the IDX in the period 2011-2016 amounted to 82.6%. The rest is the contribution of other variables outside the model. Keywords: Return On Asset (ROA),Fixed Effect Model (FEM) dan RandomEffect Model (REM).